2020
DOI: 10.3390/genes11091007
|View full text |Cite
|
Sign up to set email alerts
|

Leigh Syndrome in a Pedigree Harboring the m.1555A>G Mutation in the Mitochondrial 12S rRNA

Abstract: Background: Leigh syndrome (LS) is a serious genetic disease that can be caused by mutations in dozens of different genes. Methods: Clinical study of a deafness pedigree in which some members developed LS. Cellular, biochemical and molecular genetic analyses of patients’ tissues and cybrid cell lines were performed. Results: mitochondrial DNA (mtDNA) m.1555A>G/MT-RNR1 and m.9541T>C/MT-CO3 mutations were found. The first one is a well-known pathologic mutation. However, the second one does not appear to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, analysis revealed two variants m.508A>G and m.15948 A>G which is not reported on either the PhyloTree build 17 or Mitomaster for that group; the m.15948 in MT-TT is a conventional tRNA in the acceptor stem domain of threonine and the transition of A to G is considered possibly benign (29.90%) by MitoTIP. Our results are in line with other previous reported Leigh pedigrees that have showed more preference for subclades of haplogroup H; for example, H1r1 in Spanish pedigree harbouring the LS m.1555A>G Mutation in MT-RNR1 [104], and an Indian Leigh case study harbouring m.8993T>C mutation in the MT-ATP6 gene, which was found defining SNP for haplogroup H [105]. Haplogroup heterogeneity for Leigh syndrome has been reported in association with different Leigh-causing mutations; for instance, H13 has been found in association with MILS ATP6 mutant cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, analysis revealed two variants m.508A>G and m.15948 A>G which is not reported on either the PhyloTree build 17 or Mitomaster for that group; the m.15948 in MT-TT is a conventional tRNA in the acceptor stem domain of threonine and the transition of A to G is considered possibly benign (29.90%) by MitoTIP. Our results are in line with other previous reported Leigh pedigrees that have showed more preference for subclades of haplogroup H; for example, H1r1 in Spanish pedigree harbouring the LS m.1555A>G Mutation in MT-RNR1 [104], and an Indian Leigh case study harbouring m.8993T>C mutation in the MT-ATP6 gene, which was found defining SNP for haplogroup H [105]. Haplogroup heterogeneity for Leigh syndrome has been reported in association with different Leigh-causing mutations; for instance, H13 has been found in association with MILS ATP6 mutant cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…The mutations m.1555A > G and m.1494C > T have been found in multiple independent studies and are the best-characterized mtDNA mutations associated with aminoglycoside-induced and non-syndromic deafness [ 100 , 101 , 102 ]. Atypical clinical presentations of the m.1555A mutation have also been reported in individual pedigrees affected by hearing loss and cardiomyopathy or Leigh syndrome [ 103 , 104 ]. Both 1555 and 1494 bases are located in the highly conserved decoding region of the 12S rRNA in apposition to each other but do not form a base pair.…”
Section: Mitoribosome Biogenesis and Diseasementioning
confidence: 99%
“…Mitochondrial disease is not complicated by inner ear deformity and auditory nerve dysplasia, and it causes mostly post-lingual deafness in adults [ 51 ]. The number of cochlear spiral ganglion cells in patients with the common mtDNA A1555G mutation remains significant, and the effect of cochlear implantation mainly depends on the residual number of the spiral ganglion and the integrity of the auditory nerve [ 52 ]. Doerfer et al [ 53 ] reported the postoperative effects of 25patients with mitochondrial deafness implanted with cochlear implants, all of which had severe SNHL.…”
Section: Discussionmentioning
confidence: 99%